Plasma free fatty acid concentrations in school children with and without abdominal (2017)
ABSTRACT: Background and objectives: In adults with abdominal obesity (AO), increased concentration of free fatty acids (FFAs) is associated with cardiometabolic risk factors. However, this association remains controversial in children. This study aimed to compare plasma FFAs concentration in children with and without AO, and to examine FFAs associations with cardiometabolic risk factors. Methods: Twenty-nine children with AO were matched, one by one, according to sex and age, with 29 non-obese peers. Abdominal obesity was classified using the ninety percentile from the IDEFICS-Study (Identification and prevention of Dietary- and lifestyle-induced health EFfects In Children and infantS). Fasting plasma glucose, insulin, and lipids were determined by colorimetric and enzymatic methods. Plasma FFAs were analyzed by gas chromatography. Results: Seventeen boys and twelve girls with similar average age (7.1 ± 2.6 vs 7.2 ± 2.7 y; p>0.05) were included in each group. Children with AO showed higher body mass index (BMI) (19.7 vs 15.4 kg/m2; p<0.001), waist circumference (64.9 vs 53.7 cm; p<0.001), systolic blood pressure (98.6 vs 93.5 mmHg; p<0.01) and fasting insulin (70.2 vs 42.4 pmol·L; p<0.05). There were not significant differences in plasma total FFAs concentration between groups. However, children with AO had higher palmitoleic acid (0.94 vs 0.70 wt%; p<0.05) and dihomo-gamma linoleic acid (2.76 vs 2.07 wt%; p<0.05). Palmitoleic and dihomo-gamma linoleic acids correlated (p<0.05) with BMI (r=0,397; r=0,296, respectively) and waist circumference (r=0,380; r=0,276, respectively). Myristic and palmitoleic acids correlated (p<0.05) with high-density lipoprotein cholesterol (r=-0.408; r=-0.572, respectively). Conclusions: These findings suggest that abdominal obese children have different plasma FFAs concentrations than non obese peers, and the associations of FFAs with cardiometabolic risk factors are present in childhood.